2008
DOI: 10.3748/wjg.14.5327
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HBc screening in Indian blood donors: Still an unresolved issue

Abstract: anti-HBc screening and discarding large number of blood units versus considering ID NAT (Individual donor nuclic acid testing) needs to be assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 14 publications
3
35
1
Order By: Relevance
“…The varied prevalence of the core positivity has been reported in Indian studies. Dhawan et al, [5] from Chandigarh reported a core positive rate of 8.4% which was comparable to our data, whereas a high positivity rate of 18.3% was observed by Bhattacharya et al, [6] in West Bengal [Table /Fig-4]. …”
Section: Discussionsupporting
confidence: 75%
“…The varied prevalence of the core positivity has been reported in Indian studies. Dhawan et al, [5] from Chandigarh reported a core positive rate of 8.4% which was comparable to our data, whereas a high positivity rate of 18.3% was observed by Bhattacharya et al, [6] in West Bengal [Table /Fig-4]. …”
Section: Discussionsupporting
confidence: 75%
“…Earlier findings suggest that recovery from acute hepatitis B virus infection may not result in complete virus elimination; rather, the immune system keeps the virus at a very low level, leading to occult hepatitis B infection [20].…”
Section: Discussionmentioning
confidence: 99%
“…Studies from other parts of India reported occult HBV infection ranging from 21% in Kolkata (eastern India), 20.87% in New Delhi (northern India) to 0% in Chandigarh (north-western India) [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…22 In the study from Behrampur, Ganjam in Orissa, about 30.1% of total donations (220 of 729) was anti HBc positive indicating a very high rate of exposure to HBV infection among the blood donors from this region. Studies from other parts of India reported that the prevalence of anti HBV core antibody ranging from 21% in Kolkata (Eastern India), 20.9% in New Delhi (Northern India) to 8.4% in Chandigarh (Northwestern India).…”
Section: Resultsmentioning
confidence: 99%